Effectiveness of the protection action to guarantee the provision of health services to Venezuelan migrants in the department of Chocó, 2016-2021 - Asprilla Panesso, Edwin Samir; Domínguez Mosquera, Jesús Javier; Espinosa Mena, Jhonatan; Palacios Minotta, Yair Alexander; Asprilla Panesso, Edwin Samir; Domínguez Mosquera, Jesús Javier; Espinosa Mena, Jhonatan; Palacios Minotta, Yair Alexander; Asprilla Panesso, Edwin Samir; Domínguez Mosquera, Jesús Javier; Espinosa Mena, Jhonatan; Palacios Minotta, Yair Alexander (Corporación Universitaria Americana, 2024)
Introduction: This article analyzes the tutela action as an effective tool that allows the protection of the right to health of Venezuelan migrants in Chocó, in addition to studying how the migration of Venezuelans to this department has implied a high demand in the provision of essential services, such as the health service, a provision that has some notable shortcomings in its normal functioning and that has been exacerbated by the high demand generated by the attention to the migrant population. Objective: To establish thenormative tools available to Venezuelan migrants to make their right to health effective through the analysis and synthesis method. Methodology: Qualitative-descriptive, based on a review of electronic journals, articles in scientific journals, as well as consultationof official State pages on the chosen topic. Conclusions: The tutela action is a suitable mechanism used by Venezuelan migrants to protect their right to health, in addition to the Temporary Statute of Protection for Venezuelan Migrants (ETPV) as a tool that allowsdirect access to health services and prevents this right from being undermined.